2002
DOI: 10.1053/jhep.2002.35068
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive use of lamivudine reduces hepatitis B exacerbation after allogeneic hematopoietic cell transplantation

Abstract: Exacerbation of hepatitis B virus (HBV) is a serious cause of morbidity and mortality in hepatitis B surface antigen (HBsAg)-positive patients undergoing transplantation. Our aim was to evaluate the effectiveness of lamivudine to prevent hepatitis due to exacerbation of HBV in HBsAg-positive patients treated with allogeneic hematopoietic cell transplantation. We studied 20 consecutive HBsAg-positive recipients of allogeneic hematopoietic cell transplantation who received lamivudine 100 mg daily starting one we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 46 publications
3
119
0
7
Order By: Relevance
“…This will lead to the development of lamivudine resistance caused by point mutations, with substitution of either valine or isoleucine for the amino acid position 204 methionine (rtM204V or rtM204I, respectively) in the HBV DNA polymerase gene (tyrosinemethionine-aspartate-aspartate [YMDD] motif) [67]. Its risk increases as the therapy is prolonged, reaching a level of 67% after 4 years in nonimmunocompromised patients Jang et al 88 Lim et al 127 Yeo et al 119 Lee et al 118 Idilman et al 117 Yeo et al 116 Leaw et al 115 Ozguroglu et al 114 Lau et al 85 Persico et al 113 Shibolet et al 112 Dai et al 111 Nagamatue et al 58 0.001 0.01 0.1 1 10 100 1000…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…This will lead to the development of lamivudine resistance caused by point mutations, with substitution of either valine or isoleucine for the amino acid position 204 methionine (rtM204V or rtM204I, respectively) in the HBV DNA polymerase gene (tyrosinemethionine-aspartate-aspartate [YMDD] motif) [67]. Its risk increases as the therapy is prolonged, reaching a level of 67% after 4 years in nonimmunocompromised patients Jang et al 88 Lim et al 127 Yeo et al 119 Lee et al 118 Idilman et al 117 Yeo et al 116 Leaw et al 115 Ozguroglu et al 114 Lau et al 85 Persico et al 113 Shibolet et al 112 Dai et al 111 Nagamatue et al 58 0.001 0.01 0.1 1 10 100 1000…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
“…On the other hand, prolonged therapy with nucleos(t)ide analogues is associated with an increased likelihood of developing lamivudine-resistant mutants. Hence, most cancer centers would aim at discontinuing or withdrawing preemptive lamivudine as soon as possible to limit the duration of antiviral therapy [57,85,86,[111][112][113][114][115][116][117][118][119]127]. However, at the moment there is no available consensus on the optimal duration of lamivudine therapy.…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
“…Earlier studies have suggested that preemptive antiviral therapy significantly reduced the risk of HBV reactivation during cytotoxic chemotherapy. 4,6,8,11 Although the concept of preemptive therapy appears appealing, it has never been investigated prospectively in HCC patients. Moreover, transarterial chemotherapy seems to be different from systemic chemotherapy in terms of the route of administration and the toxicity of the treatment itself.…”
mentioning
confidence: 99%
“…18,19 In this study, faster reduction of HBV viral loads to undetectable levels in the entecavir group also suggests that entecavir possesses better antiviral activity than lamivudine, and this may be another reason for the lower incidence of HBV reactivation seen in the entecavir group vs the lamivudine group. [20][21][22] In this study, in patients receiving transplants from donors with a natural immunity to HBV (HBsAb and HBcAb positive), both entecavir and lamivudine produced higher rates of HBsAg seroclearance and shorter times to HBsAg seroclearance than those reported in chronic HBV-infected patients. 23 These results were similar to findings of several previous studies that reported a HBsAg seroclearance rate of ∼ 70% and a median onset time of ∼ 2.4 months (range: 1.5-3.5 months) in allo-HSCT recipients.…”
Section: Discussionmentioning
confidence: 67%